Forming Buried Junctions to Enhance the Photovoltage Generated by Cuprous Oxide in Aqueous Solutions1. (3rd October 2014) - Dai, Pengcheng; Li, Wei; Xie, Jin; He, Yumin; Thorne, James; McMahon, Gregory; Zhan, Jinhua; Wang, Dunwei
Abstract Whereas wide‐bandgap metal oxides have been extensively studied for the photooxidation of water, their utilization for photoreduction is relatively limited. An important reason is the inability to achieve meaningful photovoltages with these materials. Using Cu2O as a prototypical photocathode material, it is now shown that the photovoltage barrier can be readily broken by replacing the semiconductor/water interface with a semiconductor/semiconductor one. A thin ZnS layer (ca. 5 nm) was found to form high‐quality interfaces with Cu2O to increase the achievable photovoltage from 0.60 V to 0.72 V. Measurements under no net exchange current conditions confirmed that the change was induced by a thermodynamic shift of the flatband potentials rather than by kinetic factors. The strategy is compatible with efforts aimed at stabilizing the cathode that otherwise easily decomposes and with surface catalyst decorations for faster hydrogen evolution reactions. A combination of NiMo and CoMo dual‐layer alloy catalysts was found to be effective in promoting hydrogen production under simulated solar radiation.